2013
DOI: 10.1136/bcr-2012-007820
|View full text |Cite
|
Sign up to set email alerts
|

Caecal diverticulitis, an uncommon mimic of appendicitis

Abstract: SUMMARYA 35-year-old man presented with a relatively short history of right iliac fossa pain. With an unremarkable medical history, marginally raised inflammatory markers and examination findings suggestive of acute appendicitis, a preliminary diagnosis was made and the patient listed for laparoscopic appendicectomy. However, intraoperatively, the appendix was deemed normal and, following further exploration, appendicectomy and amputation of an obviously inflamed caecal pole were carried out using a TLC 75 lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…A previous study reports it is only made in 9% of the cases, and most of these patients have had previous appendectomy [14]. The definitive diagnosis of cecal diverticulitis is most commonly justified intra-operatively during exploration for suspected appendicitis [15]. We had already suspected acute appendicitis in our seven cases with no history of prior appendectomy based on the evaluation of nonspecific findings from the US together with the clinical findings and laboratory analysis, yet the definitive diagnosis was only established intraoperatively.…”
Section: Discussionmentioning
confidence: 74%
“…A previous study reports it is only made in 9% of the cases, and most of these patients have had previous appendectomy [14]. The definitive diagnosis of cecal diverticulitis is most commonly justified intra-operatively during exploration for suspected appendicitis [15]. We had already suspected acute appendicitis in our seven cases with no history of prior appendectomy based on the evaluation of nonspecific findings from the US together with the clinical findings and laboratory analysis, yet the definitive diagnosis was only established intraoperatively.…”
Section: Discussionmentioning
confidence: 74%
“…The information about the origin could not be identified for two articles [13,14]. Eighty articles (80/146, 54.8%) were published before 1980 [12–91] and 66 (66/146, 45.2%) after 1980 [2–4,7,9,11,92–151] (Figure 2, Appendix ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, another study by Lane et al reported that 40% of patients treated with diverticular excision or intravenous antibiotic therapy required later hemicolectomy because of the continuous inflammatory process [ 5 ]. Additionally, a laparoscopic approach of the cecal diverticulitis has been reported as a safe and effective therapeutic option [ 25 , 26 , 28 , 32 ]. However, the laparoscopic surgical treatment of uncomplicated cecal diverticulitis shows comparable results in the prevention of recurrence to conservative management with initial antibiotics [ 29 ].…”
Section: Discussionmentioning
confidence: 99%